Investing in Social Protection in Uganda: The Case for Universal Healthcare for Pregnant and Lactating Women, and Children under Five - Uganda Social Protection Platform (UNICEF, 2017)
This Policy Brief is part of a series and is based on the Social Protection: Investment Case developed by the Government of Uganda (2016). The business case was developed over one and a half years and rests of the best available data available at the time of drafting. Recently released GDP ﬁgures may signiﬁcantly reduce the projected cost of scaling up some of the interventions proposed in the Investment Case.